Laparoscopic treatment of a rare causes of acute abdomen; primary omental torsion - ERGENÇ, MUHAMMER; UPRAK, TEVFİK KIVILCIM (My University, 2021)
Primary omentum torsion is one of the diseases of the omentum that can lead to an acute abdomen. In thiscase report, primary omentum torsion was detected in a patient admitted to the emergency departmentwith abdominal pain and was operated on due to acute abdomen findings, and its laparoscopic treatmentwill be explained. The purpose of the case presentation is to emphasize the necessity that primary omentaltorsion should be considered in acute abdomen patients whose history and physical examination do notcomply with specific pathologies. Laparoscopic surgery can help with both the diagnosis and treatment ofthis unusual condition.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; Acute abdomen; laparoscopy; omental torsion